2016
DOI: 10.3233/jnd-150134
|View full text |Cite
|
Sign up to set email alerts
|

Non Random Distribution of DMD Deletion Breakpoints and Implication of Double Strand Breaks Repair and Replication Error Repair Mechanisms

Abstract: Our results illustrate, in a large series of patients, the important role of RE and other genomic features in DNA breaks, and the involvement of different mechanisms in DMD gene deletions: Mainly replication error repair mechanisms, but also NHEJ and potentially aberrant firing of replication origins. A combination of these mechanisms may also be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Intron 44 spans the largest length (12%) of all introns in the DMD gene, and harbors more than 25% of the deletion start points ( Tong et al, 2020 ). However, only a few previous small-sample studies have focused on the fine structure of intron 44 ( Blonden et al, 1991 ; Love et al, 1991 ; Miyazaki et al, 2009 ; Marey et al, 2016 ). The main difficulty for the sequence analysis of intron 44 may be that short-read sequencing is not adept at locating the exact breakpoints in such a large intron with tremendous repetitive regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intron 44 spans the largest length (12%) of all introns in the DMD gene, and harbors more than 25% of the deletion start points ( Tong et al, 2020 ). However, only a few previous small-sample studies have focused on the fine structure of intron 44 ( Blonden et al, 1991 ; Love et al, 1991 ; Miyazaki et al, 2009 ; Marey et al, 2016 ). The main difficulty for the sequence analysis of intron 44 may be that short-read sequencing is not adept at locating the exact breakpoints in such a large intron with tremendous repetitive regions.…”
Section: Discussionmentioning
confidence: 99%
“…Not to mention that many studies only performed MLPA and did not search for breakpoints. Recently, Marey et al (2016) mapped 39 patients with deletions starting from intron 44 based on an aCGH array, and found that 48.7% of breakpoints clustered in the distal 50 kb regions and 33.3% were clustered in regions less than 700 bp. Researchers also found that repetitive elements, and palindromic and T-A sequences were present in the vicinity of the breakpoints ( Toffolatti et al, 2002 ; Marey et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The selected flanking reads analysis in intron 44 found that microhomology or extended microhomology sequences existed around the junction reads, and one subject (D37) without microhomology sequences had long motifs (Tables and ). The above results illustrate that microhomology (Marey et al, ) and long motifs might contribute to the instability of intron 44. We further performed flanking sequence analysis around the breakpoints in all of the 37 patients, and the results illustrated that DMD gene instability did not arise from a single underlying cause.…”
Section: Discussionmentioning
confidence: 55%
“…MMRDR was hypothesized to cause replication fork stalling and template switching, which could induce complex deletion and duplication rearrangement (Lee, Carvalho, & Lupski, 2007 (Roth, Porter, & Wilson, 1985). In the present study, some of the 200 flanking regions of the breakpoints were observed to be palindromic (CTTC) and contained low-copy repeat sequences (AAAA), which could promote DNA instability (Ankala et al, 2012;Marey et al, 2016;Sen et al, 2006) and then produce a direct ligation. Additionally, small-sequence insertions and deletions were frequently found (in 14% of patients with DMD/BMD), which could be explained by repair synthesis primed by terminal homologies.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed the 1, 7, and 44 giant introns are just downstream of out-of-frame exons (1, 7, and 44), which are (not surprisingly) the DMD deletion hot spots. These three introns are also very rich in short tandem repeats (especially TTTAAA or (T)n(A) n ), which are known to cause aberrant firing of the replication fork, as frequent mechanisms responsible for micro-homology related recombination events (Marey et al, 2016). We would like to underline that these three exons are the upstream exons of regions encoding extremely important DYS domains: the actin binding domain (exon 1, although possibly dispensable, as suggested by Wein et al, 2014), the Hinge 1 (exon 7) and the nNOS binding domain, involved in DYS signaling functions (Rybakova et al, 2000).…”
Section: Dmd Deletions and Duplications: Frequency Distribution Topmentioning
confidence: 99%